Transcriptional Profiling Underscores the Role of Preprocurement Allograft Metabolism and Innate Immune Status on Outcomes in Human Liver Transplantation - Joohyun Kim, MD, PhD; Michael T. Zimmermann, PhD; Angela J. Mathison, PhD; Gwen Lomberk, PhD; Raul Urrutia, MD; Johnny C. Hong, MD (Annals of Surgery Open)
Objective:. The adverse effects of ischemia-reperfusion injury (IRI) remain a principal barrier to a successful outcome after lifesaving orthotopic liver transplantation (OLT). Gene expression during different phases of IRI is dynamic and modified by individual exposures, making it attractive for identifying potential therapeutic targets for improving the number of suitable organs for transplantation and patient outcomes. However, data remain limited on the functional landscape of gene expression during liver graft IRI, spanning procurement to reperfusion and recovery. Therefore, we sought to characterize transcriptomic profiles of IRI during multiple phases in human OLT. Methods:. We conducted clinical data analyses, histologic evaluation, and RNA sequencing of 17 consecutive human primary OLT. We performed liver allograft biopsies at 4 time points: baseline (B, before donor cross-clamp), at the end of cold ischemia (CI), during early reperfusion (ER, after revascularization), and during late reperfusion (LR). Data were generated and then recipients grouped by post-OLT outcomes categories: immediate allograft function (IAF; n = 11) versus early allograft dysfunction (EAD; n = 6) groups. Results:. We observed that CI (vs B) modified a transcriptomic landscape enriched for a metabolic and immune process. Expression levels of hallmark inflammatory response genes were higher transitioning from CI to ER and decreased from ER to LR. IAF group predominantly showed higher bile and fatty acid metabolism activity during LR compared with EAD group, while EAD group maintained more immunomodulatory activities. Throughout all time points, EAD specimens exhibited decreased metabolic activity in both bile and fatty acid pathways. Conclusions:. We report transcriptomic profiles of human liver allograft IRI from prepreservation in the donor to posttransplantation in the recipient. Immunomodulatory and metabolic landscapes across ER and LR phases were different between IAF and EAD allografts. Our study also highlights marker genes for these biological processes that we plan to explore as novel therapeutic targets or surrogate markers for severe allograft injury in clinical OLT.